Optimization of Culture Conditions for the Production of Protease from Bacillus megaterium - P. Ramesh Kannan, R. Rengasamy, R. Rajkumar*, K. R. Jayappriyan, (Journal of Ecobiotechnology, 2010)
Abstract In this Study, Bacillus megaterium was used for protease production to examine the optimal condition for its maximum accumulation. Hence the production of enzyme was investigated at various pH, temperature, NaCl concentrations and different carbon and nitrogen sources. The medium amended with 3.0% NaCl, 1.0% gelatin, 0. 4% lactose, 0.5% peptone and pH 9, incubation at 40Â°C for 42 h were supported maximum protease production of 78.5 U/ml. — Centre for Advanced studies in Botany, University of Madras, Guindy campus, Chennai- 600 025, India — Please Cite This Article As: Â R. Rajkumar*, K. R. Jayappriyan, P. Ramesh Kannan, R. Rengasamy. 2010. Optimization of Culture Conditions for the Production of Protease from Bacillus megaterium. J. Ecobiotechnol. 2(4):40-46. Â